Interstitial brachytherapy for lower lip carcinoma: Global assessment in a retrospective study of 89 cases1. Issue 3 (12th April 2012) - Rio, Emmanuel; Bardet, Etienne; Mervoyer, Augustin; Piot, Benoit; Dreno, Brigitte; Malard, Olivier
Abstract Background Infiltrating squamous cell carcinoma (SCC) of the lower lip is a highly curable cancer. We retrospectively analyzed oncologic, functional, and cosmetic outcomes after interstitial low‐dose rate brachytherapy at 58 Gy (50–62) of lower lip SCC treated in our institution. Methods There were 89 patients (44 T1, 33 T2, 2 T3, and 10 after wedge‐excision). All tumors were N0 at the time of treatment. We calculated survival rates and assessed functional and cosmetic results de visu. Results After a median follow‐up of 36 months (range, 9–127), 5‐year local control rate was 95% and 5‐year disease‐free survival was 82%. Only 6 patients (5 T2 and 1 T3) developed secondary cervical nodal involvement. Sixty‐one patients were reassessed and 11 patients presented mild functional troubles. Cosmetic results were good (77%) or fair (21%). Conclusion Brachytherapy provided a high local disease control rate, excellent functional results, and good cosmetic outcomes for SCCs of the lip. Risk of cervical node involvement was low with small tumors. © 2012 Wiley Periodicals, Inc. Head Neck, 2013